Usefulness of cash flow in business decision making - Amran, Noor Afza; Ali Abdi, AbdiNassir (2012)
This research examines the relationship between free cash flows with earnings, dividend per share, depreciation, and capital expenditures.Using a sample of 100 companies listed on Bursa Malaysia between 2005 until 2010, this study applies ordinary least squares and fixed-effects method to estimate the regression model.Findings reveal that Earnings Before Interest,Taxes, Depreciation and Amortisation(EBITDA), Capital Expenditure and Depreciation significantly influence the Free Cash Flows.EBITDA and Capital Expenditure has shown positive relationship with free cash flow, but Depreciation reflects a negative relationship with free cash flow.These findings may provide useful information to investors and businessmen on how to plan and manage the cash flow.